Size-and phase-dependent structure of copper(ii) oxide nanoparticles1. Issue 44 (16th May 2015) - Ahmed, Alauddin; Elvati, Paolo; Violi, Angela
<x xml:space="preserve">Abstract</x> Core (3 nm diameter) and outer surface layer (0.5 nm width) of a CuO nanoparticle of 4 nm in diameter.